UV curing of a liquid based bismaleimide-containing polymer system (eXPRESS Polymer Letters, 2007)
A new liquid formulation of commercial bismaleimide and n-acryloylmorpholine was prepared that could be UV cured as an alternative to traditional thermal cure methods presently used for BMI in the industry. UV curing was shown to be an efficient method which promoted the reaction rate significantly and was able to achieve this at low temperatures (30–50°C). A free radical polymerization approach has been used to explain the cure mechanism and cure kinetics, using data elucidated from the DPC and FTIR. The cured thin film was shown to achieve very high thermal stability (~400°C), with the BMI shown to retard the thermal degradation temperature and rate.